2021
DOI: 10.3390/biom11060794
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptides Regulate Prostate Cells Inflammatory Behavior: Potential Novel Anticancer Agents for Prostate Cancer

Abstract: Inflammation, by inducing a tumor-promoting microenvironment, is a hallmark for prostate cancer (PCa) progression. NOD-like receptor protein 3 (NLRP3)-inflammasome activation, interleukin-1β (IL-1β) secretion, and cancer cell-released extracellular vesicles (EVs) contribute to the establishment of tumor microenvironment. We have shown that PC3-derived EVs (PC3-EVs) activate inflammasome cascade in non-cancerous PNT2 cells. It is known that the endogenous biomolecules and Natriuretic Peptides (NPs), such as ANP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Prostate cancer cells secrete extracellular vesicles (EVs) loaded with pro-inflammatory molecules to modify the tumor microenvironment and promote tumor progression [ 76 ]. Mezzasoma et al reported that ANPs phosphorylated the NLRP3 receptor through the p38-MAPK pathway and then inhibited the inflammasome activation and IL-β maturation in PC3 cells, as well as reversing the inflammatory phenotypes of normal cells induced by EVs from PC3 cells [ 77 ].…”
Section: Anti-cancer Effects Of Anpsmentioning
confidence: 99%
“…Prostate cancer cells secrete extracellular vesicles (EVs) loaded with pro-inflammatory molecules to modify the tumor microenvironment and promote tumor progression [ 76 ]. Mezzasoma et al reported that ANPs phosphorylated the NLRP3 receptor through the p38-MAPK pathway and then inhibited the inflammasome activation and IL-β maturation in PC3 cells, as well as reversing the inflammatory phenotypes of normal cells induced by EVs from PC3 cells [ 77 ].…”
Section: Anti-cancer Effects Of Anpsmentioning
confidence: 99%
“…TNF signaling pathway mediates enzalutamide induced metastatic phenotype of PRAD [32]. NOD-like receptor signaling pathway contributes to the establishment of PRAD microenvironment [33]. The above results suggested that 33 PRGs play an important role in the occurrence and development of PRAD.…”
Section: Discussionmentioning
confidence: 81%
“…Previous reports were referred to select the concentration of H 2 O 2 and peptides. The Oxidative stress was induced by exposing the primary VSMC cells to H 2 O 2 (100 µM) 27 in the presence or absence of Ang1‐7, BNP, NP (1 µM) 28–30 . Time points for further studies was selected on MTT assays.…”
Section: Methodsmentioning
confidence: 99%